The Effect of Workload, Training and Reward on Frontliner Service Quality Performance with Motivation as an Intervening Variable - Leonarda, Olivia; Aima, M. Havidz; Lusiana, Lusiana (Journal La Sociale, 2024)
This study aims to analyze the influence of workload, training, and rewards on the service quality performance of frontliners at PT Private Bank X, with motivation as an intervening variable. The research is grounded in the critical role of frontliners in delivering customer-facing services, which are affected by factors such as workload, training, and rewards. The research questions focus on the extent to which these three variables impact service quality performance through motivation. The study employs a quantitative approach using multiple regression analysis and mediation testing to evaluate the role of motivation. The findings indicate that workload has a significantly negative impact on frontliner performance, whereas training and rewards have a significantly positive effect. Moreover, motivation serves as an intervening variable that strengthens the influence of training and rewards on service quality performance but does not enhance the impact of workload. These results suggest that to enhance service quality performance, the company should focus on improving training programs and providing appropriate rewards while effectively managing workload to prevent a decrease in employee motivation.